2006
DOI: 10.1111/j.1442-9071.2006.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of excitotoxicity in the pathogenesis of glaucoma

Abstract: Excitotoxicity describes the process of neuronal injury by excess stimulation of amino acid receptors. This form of insult was first described in the retina, and subsequently has been shown to be an important component of the pathogenesis of ischaemic and traumatic injury in the central nervous system. Furthermore, there is increasing evidence that excitotoxicity is involved in several chronic neurological conditions, and anti-excitotoxic treatment has already been approved for some of these conditions. A larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 105 publications
1
118
0
2
Order By: Relevance
“…16,17 Glutamate is a transmitter that exists widely in the brain and medulla spinalis, and is responsible for 75% of excitatory transmission. 1,[4][5][6] Glutamate triggers oxidative injury and free radical injury. It is also able to stimulate nitric oxide formation, which is an important free radical precursor, by activating nitric oxide synthase (iNOS or NOS-2) enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16,17 Glutamate is a transmitter that exists widely in the brain and medulla spinalis, and is responsible for 75% of excitatory transmission. 1,[4][5][6] Glutamate triggers oxidative injury and free radical injury. It is also able to stimulate nitric oxide formation, which is an important free radical precursor, by activating nitric oxide synthase (iNOS or NOS-2) enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…3 Glutamate is an important transmitter existing widely in the central nervous system (CNS) and is responsible for excitatory transmission. 1,[4][5][6] Its neurotoxic effect (excitotoxicity) was first seen through experimental studies on mice. 4 In further studies, it was determined that glutamate may be effective in the pathogenesis of some neurodegenerative diseases of CNS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excitotoxicity, the mechanism involved in the pathogenesis of neurological diseases, including stroke, motor neuron disease (MND), Alzheimer's disease (AD), retinal ischemia and glaucoma [1-12], is classically considered as a somatodendritic insult due to prolonged or excessive activation of excitatory amino acid receptors. Studies have also indicated axonopathy as an early feature in neurodegenerative diseases associated with excitotoxicity [13-16].…”
Section: Introductionmentioning
confidence: 99%